Hybrid Progression

Calculus Level 3

3 , 6 , 9 , 12 , 3 , 9 , 27 , 81 , \begin{aligned} && 3, 6,9,12,\ldots \\ && 3, 9,27,81,\ldots \\ \end{aligned}

The above shows two rows of numbers, each of these rows has infinitely many numbers.
The first row of numbers follows an arithmetic progression , whereas
The second row of numbers follows a geometric progression .

We know that the sum of all the numbers in each row diverges to infinity .
However, the sum of the ratio of each term exists! What is it?

In other words, what is the value of

3 3 + 6 9 + 9 27 + 12 81 + ? \dfrac33 + \dfrac69 + \dfrac9{27} + \dfrac{12}{81} + \cdots \, ?


The answer is 2.25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sabhrant Sachan
Jun 25, 2016

n t h Term of sequence : T n = 3 n 3 n n 3 n 1 , n N Let the sequence be S S = 1 3 0 + 2 3 1 + 3 3 2 + + n 3 n 1 1 3 S = 1 3 1 2 3 2 n 1 3 n 1 n 3 n Add these two equation 2 3 S = 1 + 1 3 + 1 3 2 + + 1 3 n 1 n 3 n 2 3 S = 1 1 3 n 1 1 3 n 3 n S = 3 2 ( 3 2 ( 1 1 3 n ) n 3 n ) lim n S = 9 4 = 2.25 \quad n^{th} \text{ Term of sequence : } T_{n} = \dfrac{3n}{3^n} \implies \dfrac{n}{3^{n-1}} \quad , \quad n \in \mathbb N \\\quad \text{Let the sequence be S} \\\quad S = \dfrac{1}{3^0}+ \dfrac{2}{3^1}+ \dfrac{3}{3^2}+\cdots+ \dfrac{n}{3^{n-1} } \\ \quad -\dfrac{1}{3}S =-\dfrac{1}{3^1}- \dfrac{2}{3^2}-\cdots-\dfrac{n-1}{3^{n-1} }-\dfrac{n}{3^{n} } \\ \quad \text{Add these two equation } \\ \quad \dfrac{2}{3}S= 1+\dfrac13+\dfrac{1}{3^2}+\cdot+\dfrac{1}{3^{n-1}}-\dfrac{n}{3^{n}} \\ \quad \dfrac{2}{3}S = \dfrac{1-\frac{1}{3^n}}{1-\frac13}-\dfrac{n}{3^n} \\ \quad \boxed{S=\dfrac{3}{2}\left(\dfrac{3}{2}\left(1-\frac{1}{3^n}\right)-\dfrac{n}{3^n}\right)} \\ \quad \displaystyle \lim_{n \to \infty} S = \dfrac{9}{4} = \boxed{2.25}

Rajbir Malik
Jun 25, 2016

n/(3^(n-1))=(1/3)×(n-1)/(3^(n-2))+1/(3^(n-1)) Taking summation from n=1 to infinity, we get, S=S/3 + 1.5, => S=2.25

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...